Tradução de modelos de redes de automatos estocásticos para a linguagem do NUSMV - Wondracek, Alberto do Carmo Sulzbacher (2013)
Stochastic Automata Network (SAN) is a formalism that allows the description of systems in order to evaluate them quantitatively. The aim of this work is to enable the qualitative evaluation on SAN models through its translation to the language of an existent model checker. This work proposes, details and exemplifies the mapping of a subset of SAN models to the NuSMV input language. As observed, the NuSMV models generated by the translator preserve the semantic of its originals SAN models because they have an isomorphic transition state system. The model checking through CTL (Computation Tree Logic) on SAN models is exemplified as well